CROSS-CULTURAL VARIATIONS IN CONSUMER BEHAVIOR: A LITERATURE REVIEW OF INTERNATIONAL STUDIES (The South East European Journal of Economics and Business, 2018)
The purpose of this paper is to present a review of 85 international studies of cross-cultural variations in consumer behavior, conducted in 2000–2016; to systemize conceptual and methodological approaches to research of cross-cultural variations in consumer behavior; to identify conceptual and methodological gaps and empirical issues in these studies; to pose research questions; and to set directions for future research. This literature review reveals the lack of a unified conceptual approach to defining cross-cultural variations and the absence of a unified terminology related to cross-cultural research. It also highlights methodological areas susceptible to common method bias, which hinders the establishment of equivalence in studies of cross-cultural variations in consumer behavior. This review accentuates the “cross-cultural variations” concept in consumer behavior research covering both differences and similarities, which are the subject of cross-cultural studies.